Under-Reporting and Under-Recording of Hate Crimes against Muslim Women in Italy: Cinzia Broccolo, Rūta Grigaliūnaitė, Cloé Saint-Nom, Guido Savasta - Meško, Gorazd; Kutnjak Ivković, Sanja; Hacin, Rok (The UN Sustainable Development Goals and Provision of Security, Responses to Crime and Security Threats, and Fair Criminal Justice Systems, 2024)
The chapter analyses the root causes of under-reporting (the low number of reports from victims and witnesses), which causes a lack of recognition of the discriminatory matrix of reported crimes and, therefore, under-recording (erroneous reporting and investigation – by law enforcement agencies) of hate crimes against Muslim women in Italy. A survey of practitioners and members of the Muslim community in Italy was conducted between May and September 2022. The findings reveal that multiple factors contribute to the low reporting rate and the flaws in recording episodes of hate speech and hate crimes of intolerance and hatred towards Muslim women. Lack of trust in the judiciary or the police and the significant “tendency” to not report a case of intolerance represent the main causes of under-reporting. This brings out a habituation of victims towards hate and discrimination.